Dilema Etika dan Tanggung Jawab Profesi Hukum dalam Era Digital: Studi Kasus Pelanggaran Kode Etik oleh Oknum Penegak Hukum pada Kasus Ferdy Sambo dan Pembunuhan Brigadir J (2022) - Puspadewi, Gladys Trias; Purba, Moses Frederick; Alvito, Haykal Rizki; Haryani, Diah Septi; Valentara, Aqiila Banyu; M, Mulyadi (Media Hukum Indonesia (MHI), 2025)
The rapid development of digital technology has had a significant impact on various sectors, including the legal world. The digital era has given rise to various new challenges for law enforcers, especially related to violations of the code of ethics and professional responsibility. This study aims to examine the ethical dilemma and responsibility of the legal profession in dealing with violations of the code of ethics by law enforcers in the digital era. This study uses a qualitative approach by analyzing various cases of violations of the code of ethics involving law enforcers, as well as their impact on the credibility and integrity of the legal profession in society. The results of the study indicate that the digital era exacerbates the spread of inaccurate information and often worsens the image of the legal profession. Enforcement of the code of ethics of the legal profession requires adaptation to technological developments and the implementation of stricter supervision. This study also highlights the importance of the role of supervisory institutions and professional education in strengthening commitment to the ethics of the legal profession in the digital era. It is hoped that the findings of this study can provide insight into the development of legal profession policies and practices that are more responsive to changes in the times.